Francja wyzwolona. (Gdynia : [s.n.], 1946)
Afisz filmu, który był wyświetlany w gdyńskim kinie ok. marca 1946 r.
Keywords: Kina -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Kino sowieckie -- 1945-1960 -- druki ulotne; Kino francuskie -- 1945-1960 -- druki ulotne